(untitled) (Revista Brasileira Multidisciplinar, 2024)
This work deals with the study of the stability of a body cream with rosemary oil in comparison with the cream without rosemary essential oil. The research was carried out in the pharmacology laboratory of the Federal Institute of Palmas/PR, Campus Palmas. The fresh rosemary plant material collected was subjected to Essential Oil extraction by hydrodistillation with Clevenger, during a period of two hours at boiling temperature. Rosemary essential oil was incorporated into a moisturizing fluid at 0.5% composition. To monitor the behavior of the stability of the emulsions, the methodologies proposed by the Brazilian Pharmacopoeia were followed. Centrifugation, pH, freezing and thawing cycle and density tests were performed. The oil yield was 0.1047%, lower than the findings in the literature 0.30%, which can be attributed to the different edaphoclimatic conditions to which the plants are subjected. With regard to the preliminary stability of the tested lotion, it can be said that the addition of rosemary essential oil did not negatively impact the base lotion, since the parameters of density, pH and appearance after freezing, thawing and centrifugation did not show related changes. product degradation. A positive point observed in relation to the addition of oil to the lotion was that the pH of the product was close to the cutaneous pH, different from the base lotion used.